BAHASA RUPA KOMIK WAYANG KARYA R.A. KOSASIH - Sayid Mataram (Institut Seni Indonesia Surakarta, 2015)
Comic is a media of speech, like a language is, with the language system and individual application. Comicof puppet by R.A. Kosasih is one of the genres in constellation of Indonesia comic which is able to overcomethe influence of western comic. The problems analyzed in this research include how the form of visuallanguage and idiolect characteristics of puppet comic by R.A. Kosasih. This research aims to analyze thevisual language of puppet comic by R.A. Kosasih as well as the idiolect characteristic that is appeared to beits characteristic. The research uses an approach of language analogy using textual and contextual analysisof comic. The result shows that firstly, the visual language of comic is analog with language consisting oflanguage system and idiolect. The system of visual language in comic R.A. Kosasih consists of the basicelements of comic constituent covering panel and juxtaposition structure. Secondly, puppet comic by R.A.Kosasih uses stories based on Mahabarata epos and Ramayana in Indian version as well as Nusantarapuppet in which Sunda language is inserted. The picture and symbol in the comic is influenced by the realiststyle of Western comic and Indie Mooi stream and also the technology of the age. The relationship of puppetcomic juxtaposition is influenced by the story order and the session of lakon.Keywords: comic, language, visual, puppet, idiolect